The post-COVID-19 rise in labour shortages - Causa, Orsetta (OECD Publishing, 2022)
The labour market recovery from the COVID-19 pandemic has been strong among advanced countries, partly reflecting massive and unprecedented policy support to workers and firms. This paper provides evidence and stylised facts about labour market tightening and labour shortages since the onset of the pandemic. Labour shortages have been widespread across countries, yet particularly in Australia, Canada and the United States; and across industries, yet particularly in contact-intensive ones like accommodation and food, but also manufacturing. This picture is to a good extent driven by cyclical factors: in tight labour markets, workers are more likely to switch for better job opportunities. But this paper argues, based on illustrative evidence, that other factors beyond the economic cycle may also play a role: the post-COVID-19 increase in labour shortages may partly reflect structural changes, in particular changes in preferences, as some workers may no longer accept low-pay and poor or strenuous working conditions
Keywords: Economics